2019
DOI: 10.1177/1474515119888813
|View full text |Cite
|
Sign up to set email alerts
|

Patient-reported outcomes at hospital discharge among patients with arrhythmia: Results from the national DenHeart survey

Abstract: Background: Patient-reported outcomes are important predictors of mortality, cardiovascular events and hospitalisation in patients with cardiac diseases, but differences in patient-reported outcomes between groups of patients with arrhythmia have not yet been investigated. Aims: To describe and compare patient-reported outcomes at discharge among patients with different types of cardiac arrhythmia and to examine the associations between demographic characteristics, inhospital factors and patient-reported outco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 38 publications
2
0
0
Order By: Relevance
“…We found that depression and anxiety symptoms at discharge were associated with readmissions. This is consistent with findings among other groups of patients with heart disease, including those with dysrhythmias 33–35 . Our findings are also comparable with those of the Danish CopenHeart survey, which included patients 6 to 12 months after ablation for AF or atrial flutter and found that all-cause readmissions were associated with symptoms of anxiety (odds ratio, 2.9; 95% CI, 1.7–5.9) and depression (odds ratio, 1.7; 95% CI, 1.0–3.0) 4 .…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…We found that depression and anxiety symptoms at discharge were associated with readmissions. This is consistent with findings among other groups of patients with heart disease, including those with dysrhythmias 33–35 . Our findings are also comparable with those of the Danish CopenHeart survey, which included patients 6 to 12 months after ablation for AF or atrial flutter and found that all-cause readmissions were associated with symptoms of anxiety (odds ratio, 2.9; 95% CI, 1.7–5.9) and depression (odds ratio, 1.7; 95% CI, 1.0–3.0) 4 .…”
Section: Discussionsupporting
confidence: 90%
“…This is consistent with findings among other groups of patients with heart disease, including those with dysrhythmias. [33][34][35] Our findings are also comparable with those of the Danish CopenHeart survey, which included patients 6 to 12 months after ablation for AF or atrial flutter and found that allcause readmissions were associated with symptoms of anxiety (odds ratio, 2.9; 95% CI, 1.7-5.9) and depression (odds ratio, 1.7; 95% CI, 1.0-3.0). 4 The mechanisms by which psychological factors lead to readmissions include stimulating the autonomic nervous system, triggering the production of catecholamines, increasing blood pressure, decreasing plasma volume, and contributing to the contraction of coronary arteries, thrombocyte activity, coagulation, and inflammation.…”
Section: Discussionsupporting
confidence: 82%